Emergencies in paediatrics and neonatology. Issue 1 (22nd December 2008) - Thomson, J
Abstract : Edited by Stuart Crisp, Jo Rainbow. Published by Oxford University Press, Oxford, 2007, pp 352, £19.95 (soft cover). ISBN 978-0-19-856866-7